2001
DOI: 10.1074/jbc.m108266200
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Characterization of a Purified NS2/3 Protease Variant of Hepatitis C Virus

Abstract: The cleavage of the hepatitis C virus polyprotein between the nonstructural proteins NS2 and NS3 is mediated by the NS2/3 protease, whereas the NS3 protease is responsible for the cleavage of the downstream proteins. Purification and in vitro characterization of the NS2/3 protease has been hampered by its hydrophobic nature. NS2/3 protease activity could only be detected in cells or in in vitro translation assays with the addition of microsomal membranes or detergent. To facilitate purification of this poorly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
2

Year Published

2003
2003
2009
2009

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 34 publications
5
41
2
Order By: Relevance
“…However, the fusion of NS2 to the N terminus of NS3 does not completely abolish the interaction with NS4A. In fact, several groups have reported synthetic 4A peptides as potent inhibitors of NS2/3 autoprocessing (19,48). Nevertheless, we found a decrease in NS3 protease kinetics in an in vitro assay dependent on the addition of a 4A peptide using purified NS2/ 3-(904 -1206).…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…However, the fusion of NS2 to the N terminus of NS3 does not completely abolish the interaction with NS4A. In fact, several groups have reported synthetic 4A peptides as potent inhibitors of NS2/3 autoprocessing (19,48). Nevertheless, we found a decrease in NS3 protease kinetics in an in vitro assay dependent on the addition of a 4A peptide using purified NS2/ 3-(904 -1206).…”
Section: Discussioncontrasting
confidence: 53%
“…No homology between NS2/3 and other proteases has been identified, and the catalytic mechanism of action remains unclear. Although the observation that NS2/3 activity is stimulated by zinc and inhibited by EDTA has led some groups to suggest that NS2/3 is a novel metalloprotease, others have proposed that it may function as a cysteine protease, and studies performed with classical protease inhibitors have not yielded a definite classification (17,19,20). Mutagenesis studies have identified His 952 and Cys 993 within NS2 as being essential for NS2/3 protease activity (15,16), and in addition, mutations thought to perturb the local conformation of the cleavage site also inactivate the enzyme (21).…”
Section: Hepatitis C Virus (Hcv)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the observation that the protease activity is stimulated by metal ions and inhibited by EDTA led to the suggestion that the NS2/3 protease was a metalloprotease (27,31). Furthermore, sequence comparison with other proteases and studies with classical protease inhibitors (64,83) have not resulted in a definitive classification. Additionally, NS2/3 autoprocessing seems to be extremely sensitive to the correct folding of the protease (27,31,66), and a trans-cleavage activity of an active NS2/3 protease containing a mutant cleavage site has been suggested (66).…”
Section: Discussionmentioning
confidence: 99%
“…7A and B), the bulk of mature NS2 and NS3 should arise from processing of the nascent chain. Previous studies also noted that the posttranslational NS2-3 autocleavage is inefficient, unless special conditions (such as the presence of detergents) are met (56,78).…”
Section: Discussionmentioning
confidence: 99%